EBV infection is prevalent in the adenoid and palatine tonsils in adults. Issue 6 (5th December 2016) - Seishima, Noriko; Kondo, Satoru; Wakisaka, Naohiro; Kobayashi, Eiji; Imoto, Tomoko; Moriyama‐Kita, Makiko; Nakanishi, Yosuke; Endo, Kazuhira; Murono, Shigeyuki; Sugimoto, Hisashi; Hatano, Miyako; Ueno, Takayoshi; et al.
Abstract : Epstein‐Barr virus (EBV) is associated with the pathogenesis of several diseases in both adults and children. However, there have been no reports on the prevalence and amount of EBV in the adenoids of adults; thus, it is important to investigate these in the adenoids and tonsils of adults and children. In this study, 67 patients who underwent tonsillectomy or adenotonsillectomy were included and divided into two groups: adults aged ≥ 16 years ( n = 35) and children aged <16 years ( n = 32). Patients' adenoid and tonsil tissues were analyzed using quantitative polymerase chain reaction for EBV DNA. EBV was detected in 26 (74%) adenoids and 25 (71%) tonsils among the adult group and was detected 21 (66%) adenoids and 20 (63%) tonsils in the child group. There was no significant difference in EBV DNA prevalence between the adenoids and tonsils for each group. However, there was a significant correlation between EBV DNA load in the adenoids and tonsils of the same individual in both groups ( r = 0.579, P < 0.01, adult group; r = 0.919, P < 0.01, child group). In conclusion, EBV infection is prevalent in the adenoids and tonsils in adults and children. These results indicate that EBV continuously reside in the nasopharyngeal region after primal infection and may develop several diseases.